Social Inhibition: Theoretical Review and Implications for a Dual Social Inhibition Model within the Circumplex of Personality Metatraits - Kwiatkowska, Maria M.; Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2021)
The purpose of this paper is to present a new model of social inhibition (a) conceptualised as a dual structured construct including shyness and modesty, and (b) showing the complexity and diversity of these two social inhibition forms across various domains of psychosocial functioning (i.e., self-image, cognitive, emotional, and behavioural). Locating these two forms of social inhibition within the space of the Circumplex of Personality Metatraits enabled us to identify conceptually adjacent constructs to social inhibition and put the latter into a broad personality context. Through supplementary meta-analyses of the relations of shyness and modesty with the Big Five personality traits, we confront our theoretical proposition with existing empirical findings. Our paper implies that social inhibition might be successfully treated as a psychosocial disposition with two related and shared core elements, but distinct and differentially targeted forms—more neurotic and dysfunctional shyness and more agreeable and adaptive modesty.